Development and validation of multivariable clinical diagnostic models to identify type 1 diabetes requiring rapid insulin therapy in adults aged 18-50 years - Lynam, A; McDonald, T; Hill, A; Dennis, J; Oram, R; Pearson, E; Weedon, M; Hattersley, A; Owen, KR; Shields, B; Jones, A (BMJ Publishing Group, 2019)
Abstract Objective To develop and validate multivariable clinical diagnostic models to assist distinguishing between type 1 and type 2 diabetes in adults aged 18–50.